(untitled) (Texas Journal of Philology, Culture and History, 2026)
This study is devoted to the examination of Eastern motifs in 18th-century German dramaturgy. The focus is on the process of formation and artistic interpretation of the image of the East in the works of German playwrights of the Enlightenment era. The paper analyzes the features of representing Eastern culture, philosophy, and aesthetics, as well as their influence on the development of theatrical art in Germany. Special attention is given to the interpretation of exotic plots, images, and symbols that were used by authors to express the moral, political, and cultural ideas of their time. The research highlights the role of Eastern themes in broadening the artistic horizons of German dramaturgy and their contribution to intercultural dialogue in the 18th century